A New Approach Using Modeling to Interpret Measured Changes in Soil Organic Carbon in Forests; The Case of a 200 Year Pine Chronosequence on a Podzolic Soil in Scotland - Ražauskaitė, Rita; Vanguelova, Elena; Cornulier, Thomas; Smith, Pete; Randle, Tim; Smith, Jo U. (Frontiers in Environmental Science, 2020)
Scotland is continuing to afforest land in order to combat climate change, but the long-term capacity for carbon sequestration in forest soils is still uncertain. Here we present measurements that provide comparative estimates of soil organic carbon in grassland and forestry sites at steady state. We develop a new approach to interpret these values based on simulation of organic carbon turnover in soils that are accumulating carbon and use this to determine losses due to management operations associated with afforestation of grassland and deforestation/reforestation of forest stands. Soil organic carbon stock changes were studied in a >120 year-old Scots pine chronosequence and adjacent grassland sites on podzolic soils. Significant carbon accumulation was measured in the top organic soil horizons with forest age, while no changes were noted in the deeper mineral soil horizons. The simulations with the RothC-26.3 model revealed that pine forests on sandy soils could lose a significant amount of soil organic carbon through management operations. The lowest modeled stocks of soil organic carbon were not in the young sites (0–25 years old), but at 43 years since reforestation. Using measured data from our study site, the simulations of grassland afforestation suggested that accumulation of organic carbon under forest occurs mainly in the organic horizons, while the deeper sandy mineral soil horizons are likely to become depleted in organic carbon compared to grasslands. Our simulations suggest that afforestation of grasslands would increase overall soil carbon stocks but may deplete the more stable carbon pools in the deeper mineral horizons of the podzols.